Quality and Biochemical Characteristics of Frozen Semen of Purebred and Crossbred Bulls - Samanta, Saptadip; Jana, Subhajit; Rakshit, Subham; Singh, Rahun; Dassarma, Barsha; Bera, Sayan Jyoti; Maiti, Bidisha (The Indian Journal of Animal Reproduction, 2024)
In the present study, frozen semen straw were collected from the bull semen bank and performed routine semen analysis.  We also studied different biochemical parameters of seminal fluid, including ROS generation and DNA fragmentation.  Average viability and motility of sperm showed within 77% and 27%, respectively, which is not satisfactory. Biochemical  constituents like glucose, fructose, total protein, cholesterol, and others varied among the different breeds, and there  was no superiority among the breeds. The results of different electrolyte concentrations were closely associated among  the different breeds that protected the sperm from osmotic lysis. Aspartate transaminase, alanine transaminase, alkaline  phosphatase, and acid phosphatase activity were mostly better in exotic and crossbred breeds than in pure indigenous  breeds. Antioxidant profile and oxidative stress (OS) were also studied. The results indicated that antioxidant enzyme  (catalase, GPx) activity and reduced glutathione content were high in the crossbred variety. However, lipid peroxidation  rate was high in the Gir breed. Flowcytometry study revealed that the ROS generation level was very high, and the rate  of DNA fragmentation was around 50%, which indicated the loss of 50% of sperm due to ROS. In conclusion, it could be  said that cryopreservation decreases sperm viability, motility, and increases ROS that is detrimental to sperm survival.
Keywords: Semen; seminal fluid; Biochemical constituents; ROS, Antioxidants; DNA fragmentation